Moving across Status Lines: Low Concern for the Ingroup and Group Identification. (September 2015) - Kulich, Clara; Lorenzi‐Cioldi, Fabio; Iacoviello, Vincenzo; Stroebe, Katherine; de Lemus, Soledad
<x xml:space="preserve">Abstract</x> This research examines individuals' concern for the ingroup when they move from a socially disadvantaged inherited background (in terms of gender, ethnicity, and nationality) to a higher social standing through individual achievement. Studies 1–2 show that the status inconsistency between the disadvantaged and the achieved groups undermines concern for the disadvantaged ingroup. Studies 3–4 demonstrate that this lower concern for the ingroup is concomitant with maintaining the identification with the low‐status ingroup and the increase of the identification with the achieved group. These findings suggest that low concern for the ingroup is not explained by a decrease in identification with the disadvantaged, but rather by an increase in identification with the high‐status group.